E-Book William Flexion Exercise on Myogenic Low Back Pain - Wanti Hasmar; Faridah (Indonesian Journal of Advanced Research, 2023)
Myogenic low back pain is pain related to stress or strain on the back muscles, tendons and ligaments which are usually present when carrying out daily activities excessively. Low back pain needs to get attention because it can become a problem such as lost work time, reducing work productivity. This research is a quasi-experimental study with a one group pre-test post-test design. The sample in this study amounted to 10 people. The sampling technique is by means of proportional stratified random sampling. The results showed that after doing the william flexion exercise using a control sheet it was effective in reducing low back pain and increasing functional activity of the back and had not made positive changes for batik craftsmen who experienced myogenic lower back pain due to the need for more routine supervision and detailed control.